Wealth transfer through private placements: Evidence from China. Issue 2 (1st October 2019) - Lin, Jing; Zheng, Steven X.; Zhou, Mingshan
Abstract: We examine private issuance of public equity (PIPE) in China, and our results suggest that PIPE investors benefit from the price manipulation before and after issuance. These investors tend to cash out after lockup expiration and make large profits. We also find evidence that the trading of PIPE investors after lockup expiration is informed. Tests about the abnormal returns in the 3 years after lockup expiration suggest that at least part of the benefits PIPE investors receive come from wealth transfer from outside investors. Overall, PIPE issuers in China seem to use an opaque mechanism to compensate PIPE investors.